2003
DOI: 10.4049/jimmunol.170.1.421
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Stromal Cell-Derived Factor-1/CXC Chemokine Ligand 12 Enhances Myeloid Progenitor Cell Survival/Antiapoptosis In Vitro in Response to Growth Factor Withdrawal and Enhances Myelopoiesis In Vivo

Abstract: Hemopoiesis is regulated in part by survival/apoptosis of hemopoietic stem/progenitor cells. Exogenously added stromal cell-derived factor-1 ((SDF-1)/CXC chemokine ligand (CXCL)12) enhances survival/antiapoptosis of myeloid progenitor cells in vitro. To further evaluate SDF-1/CXCL12 effects on progenitor cell survival, transgenic mice endogenously expressing SDF-1/CXCL12 under a Rous sarcoma virus promoter were produced. Myeloid progenitors (CFU-granulocyte-macrophage, burst-forming unit-erythroid, CFU-granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
143
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 35 publications
6
143
4
1
Order By: Relevance
“…Under these diff erent conditions, although the Cxcr4 Ϫ / Ϫ HSC compartment was preserved in mice treated with tamoxifen, it was " lost " in mice that received poly I/poly C. At present, the precise reason for this discrepancy cannot be ascertained, but might be related to a distinct role of CXCR4 in HSC survival in homeostatic state or under hematologic stress caused by poly I/poly C treatment. CXCL12 has been reported to enhance survival of primitive hematopoietic cells ( 23,24 ), and of myeloid progenitor cells after cytokine withdrawal ( 25 ). Although we did not observe any changes in apoptosis of freshly isolated Cxcr4 Ϫ / Ϫ HSCs as compared with the WT HSCs, it is possible that the survival of Cxcr4 Ϫ / Ϫ HSCs is impaired under stress conditions, thereby compromising hematologic recovery from chemoablation such as poly I/poly C treatment.…”
Section: Discussioncontrasting
confidence: 52%
“…Under these diff erent conditions, although the Cxcr4 Ϫ / Ϫ HSC compartment was preserved in mice treated with tamoxifen, it was " lost " in mice that received poly I/poly C. At present, the precise reason for this discrepancy cannot be ascertained, but might be related to a distinct role of CXCR4 in HSC survival in homeostatic state or under hematologic stress caused by poly I/poly C treatment. CXCL12 has been reported to enhance survival of primitive hematopoietic cells ( 23,24 ), and of myeloid progenitor cells after cytokine withdrawal ( 25 ). Although we did not observe any changes in apoptosis of freshly isolated Cxcr4 Ϫ / Ϫ HSCs as compared with the WT HSCs, it is possible that the survival of Cxcr4 Ϫ / Ϫ HSCs is impaired under stress conditions, thereby compromising hematologic recovery from chemoablation such as poly I/poly C treatment.…”
Section: Discussioncontrasting
confidence: 52%
“…7 CXCL12 also enhances the survival/antiapoptosis of hematopoietic progenitor cells in vitro and in vivo. 8 Experiments using knockout mice have revealed that depleting CXCL12-abundant reticular cells leads to reduced hematopoietic stem cell numbers. 5 Morphologically, CXCL12-abundant reticular cells have long processes and are scattered throughout the murine bone marrow as a network.…”
mentioning
confidence: 99%
“…54 SDF-1 alone and in synergy with other cytokines enhances survival of primitive hematopoietic cells. 37,38,51,61 Therefore, the possibility existed that enhancement in survival of hematopoietic progenitor cells by SDF-1 could contribute to the enhanced transduction efficiency noted. However, given that the transduction procedure was carried out in the presence of serum and other cytokines, and that we did not observe significant changes in total numbers of CFU-GM and CFU-GEMM colonies, this possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent reports. 38,62 Recent studies have shown that prolonged stimulation of cell division in vitro can lead to uncontrolled proliferation and inhibition of differentiation in hematopoietic cells. Since SDF-1 does not stimulate proliferation and alter differentiation of primitive hematopoietic cells, SDF-1-enhanced transduction seems to avoid this potential risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation